Assessing Olive Evapotranspiration Partitioning from Soil Water Balance and Radiometric Soil and Canopy Temperatures - Francisco L. Santos (Agronomy, 2018)
Evapotranspiration (ETc) partitioning and obtaining of FAO56 dual crop coefficient (Kc) for olive was carried out with the SIMDualKc software application for root zone and topsoil soil water balance based on the dual crop coefficients. A simplified two source-energy balance model (STSEB), based on daily remotely sensed soil and canopy thermal infrared data and retrieval of surface fluxes, also provided information on partitioning ETc for the olive orchard. Both models were calibrated and validated with ground-based, sap flow-derived transpiration rates, and their performance was compared in partitioning ETc for incomplete cover, intensive olive grown in orchards (≤300 trees ha−1). The SIMDualKc proved adequate in partitioning ETc. The STSEB model underestimated ETc mostly by inadequately simulating soil evaporation and its contribution to the total latent heat flux. Such results suggest difficulties in using information from the STSEB algorithm for assessing ETc and dual Kc crop coefficients of intensive olive orchards with incomplete ground cover.